Poisoning cases who admitted to the pediatrics emergency unit in the last 5 years: Evaluation of 1734 cases - Bozlu, Gülçin; Kuyucu, Necdet (The Bulletin of Legal Medicine, 2018)
Objective: Childhood poisoning is an important public health problem that can suddenly appear and it can lead to serious morbidity and mortality. In this study, we evaluated the children admitted to our pediatric emergency department due to poisoning within the last five years. Materials and Methods: Between January 1,2013 and December 31, 2017, the records of 1734 children who applied to our pediatric emergency department due to poisoning were examined retrospectively. The cases were evaluated in terms of age, gender, reason for poisoning, pharmacological agents and management. Results: In our study, the ratio of poisoning cases to all pediatric emergency admissions was 0,68%. Of those, 1020 (58.8%) were female and 714 (41.2%) were male (female to male ratio: 1.4). The mean age of the children was 9.68 ± 2.85 years (5 months-18 years) and the mean age of female was higher than that of the male (12.61 ± 2.7 years and 8.14 ± 3.7 years, respectively p= 0.07). The most frequent (%59.4) causes of poisoning were drugs and the most of them was analgesics (21.5%). 571 of the cases (32.9%) had suicide attempts. The cases were treated at pediatric emergency unit (66.2%), pediatrics department (10.9%), pediatric intensive care unit (3.5%) and pediatric surgery department (18.7%). Conclusion: Our findings showed that the most common poisoning agents in children were drugs. A considerable part of these events was suicide attempt. The measures to be taken by environment, family, drug manufacturers and physicians may prevent childhood poisoning.